BIOLOGICAL WASTEWATER TREATMENT IN CONTEXT OF CIRCULAR ECONOMY - Dzihora, Yuliia; Stolyarenko, Hennadiy (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2021)
With the beginning of Anthropocene epoch, nature is facing a lot of environmental problems that drastically increased in the last century. On the current rate of resource consumption, soon nature will lose the ability for self-restoration. In order to avoid inevitable consequences of resources exploitation, new approaches should be developed in all areas of human life. Linear economy concepts that were utilized for a long time and were based on use and disposal of each separate resource depending on the purpose is not sufficient anymore. More holistic approach should be applied to overcome the challenges that we are facing now. Application of circular economy concepts for wastewater treatment facilities has a great potential to enhance sustainability of water management. This paper will focus on circular economy concepts applied for modern pilot installation that combines biological treatment and membrane separation and discusses the potential for the full-scale implementation. Since, pilot plant was operated without any chemicals addition it eases the use of the waste sludge that is received as a by-product for different purposes as agricultural application and biogas production.